2006
DOI: 10.1111/j.1365-2796.2006.01704.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of KL‐6 and subsequent mortality in patients with interstitial lung diseases

Abstract: s. Objectives.  KL‐6 is a specific marker in patients with interstitial lung diseases (ILDs); however, the relationship between elevated levels of KL‐6 and subsequent mortality is not well defined. To determine if elevated serum levels of KL‐6 are associated with increased mortality, and to identify the most suitable cut‐off level of KL‐6 by which to distinguish between good prognosis and poor prognosis, we evaluated the prognostic significance of serum KL‐6 levels in patients with stable‐state ILDs. Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
115
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(125 citation statements)
references
References 28 publications
8
115
0
2
Order By: Relevance
“…Future studies should also consider whether sLOXL2, along with other promising prognostic IPF biomarkers (e.g. matrix metalloproteinase (MMP)1, MMP7, KL-6, periostin, surfactant protein-A and D, CC chemokine ligand 18, vascular endothelial growth factor and YKL-40) [19][20][21][22][23][24][25][26][27][28][29], as well as prognostic scores [30,31] and radiological modalities [32], might have prognostic value for helping physicians and patients anticipate the patient's IPF disease progression. This might include evaluation of serially collected sLOXL2 levels and their relationship to IPF acute exacerbations, which represent a terminal event for many IPF patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should also consider whether sLOXL2, along with other promising prognostic IPF biomarkers (e.g. matrix metalloproteinase (MMP)1, MMP7, KL-6, periostin, surfactant protein-A and D, CC chemokine ligand 18, vascular endothelial growth factor and YKL-40) [19][20][21][22][23][24][25][26][27][28][29], as well as prognostic scores [30,31] and radiological modalities [32], might have prognostic value for helping physicians and patients anticipate the patient's IPF disease progression. This might include evaluation of serially collected sLOXL2 levels and their relationship to IPF acute exacerbations, which represent a terminal event for many IPF patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…Again, as this study was performed prior to 2002, one should bear in mind that the diagnosis of IPF was since then reclassified [1]. Satoh et al reported an increased mortality in patients with an IIP, including patients with IPF, with serum levels of KL-6 > 1000 U/ml at initial measurement [33]. Furthermore, Yokoyama et al reported worse survival of IPF patients with KL-6 levels > 1000U/ml at time of presentation, in a retrospective study of a total of 27 patients [34].…”
Section: Kl-6mentioning
confidence: 99%
“…It has also been reported that KL-6 induces chemotaxis of human fibroblasts in vitro, suggesting that it may have a pathological role in fibrosing lung disease [21]. Therefore, measurement of serum KL-6 is now widely accepted as a diagnostic marker for monitoring the activity of interstitial lung diseases, such as idiopathic interstitial pneumonia, and for the long-term management of various interstitial diseases [1,2,[7][8][9][10][11]13].…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have also reported that KL-6 is a useful serum marker to confirm diagnosis and for long-term management in patients with diffuse pulmonary diseases, particularly interstitial lung diseases. Patients with idiopathic pulmonary fibrosis or non-specific interstitial pneumonia showed significantly elevated KL-6 levels [8][9][10][11][12][13].…”
mentioning
confidence: 99%